On the Evolving Nature of Exposure Therapy. (March 2013) - Schare, Mitchell L.; Wyatt, Kristin P.
Four articles examining methodological applications of exposure therapy and its limited dissemination were briefly reviewed. Methodological articles included those by Abramowitz et al., Gryczkowski et al., and Weiner and McKay, which addressed couple treatment of obsessive–compulsive disorder (OCD), modification of evidence-based anxiety treatments for children, and novel exposure methods for depersonalization and derealization, respectively. The creative aspects of these innovations are highlighted as well as historical parallels in the empirical literature for both anxiety and other clinical phenomena. Underutilization and limited dissemination concerns are discussed in the context of the fourth article by Hipol and Deacon and as related to the field as a whole. A unique concept, exposaphobia, is hypothesized to explain the lack of clinicians' utilization of this technique, due to their own anxiety-driven inhibitions in using it. Suggestions for the future of exposure research and dissemination are made.